2002
DOI: 10.2140/pjm.2002.207.345
|View full text |Cite
|
Sign up to set email alerts
|

Discrete logarithmic energy on the sphere

Abstract: In this article we consider the problem posed by Whyte, about the distribution of N point charges on the unit sphere, whose mutual distances have maximal geometric mean. Some properties of the extremal points are discussed. In the case when N = 5 the optimal configuration is established rigorously, which solves an open problem communicated by Rakhmanov.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 23 publications
1
42
0
Order By: Relevance
“…These points are referred to as either logarithmic points [11] or elliptic Fekete points [39], with mathematical origins in [16]. For small values of N , such points can be found by detailed geometrical constructions (see [11] for N = 5 and [28] for N = 6). In particular, for N = 5, it was proved in [11] that the optimal configuration for p(x 1 , .…”
Section: Previous Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These points are referred to as either logarithmic points [11] or elliptic Fekete points [39], with mathematical origins in [16]. For small values of N , such points can be found by detailed geometrical constructions (see [11] for N = 5 and [28] for N = 6). In particular, for N = 5, it was proved in [11] that the optimal configuration for p(x 1 , .…”
Section: Previous Resultsmentioning
confidence: 99%
“…For small values of N , such points can be found by detailed geometrical constructions (see [11] for N = 5 and [28] for N = 6). In particular, for N = 5, it was proved in [11] that the optimal configuration for p(x 1 , . .…”
Section: Previous Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By traditional methods (see [DLT02]) it can be shown that the triangular bi-pyramid consisting of two antipodal points at, say, the North and the South Pole, and three equally spaced points on the Equator, is the unique (up to orthogonal transformation) minimizer of the logarithmic average pair-energy. The proof that the same configuration maximizes the sum of distances (that is: assumes v −1 (5)) is computer-aided, exploiting interval methods and related techniques (see [HoSh11]).…”
mentioning
confidence: 99%